Pengaruh Konflik Terhadap Kinerja Karyawan - Nurhikmah, Nurhikmah; Halilah, Ii (POLITEKNIK NEGERI BANDUNG, 2016)
Conflict can be one of important thing that has an influence on organizational productivity because it can affect to employees performance. If the conflict can not be managed carefully it will impact to decrease performance. But in other ways, if the conflict can be managed carefully it will impact to increase performance.This study was conducted to 101 employees of PT. Astra International, Tbk - Toyota Sales Operation AUTO2000 Setiabudi Bandung. This research based on the phenomenon at PT. Astra International Tbk - Toyota Sales Operation AUTO2000 Setiabudi Bandung that conflict between sales and other sales to the struggle for customers, and employees of the workshop did mistake when making spare parts, and employees performance did not reach last two years. The purpose of this research is to determine how much influence the conflict on employee performance in PT. Astra International Tbk - Toyota Sales Operation AUTO2000 Setiabudi Bandung. In this study, the conflict is the independent variable (X) and employee performance is the dependent variable (Y). This research uses descriptive analysis method, the classical assumption test, regression, correlation, and test hypotheses in analyzing the data obtained through observation, interviews, literature review, and questionnaires. From simple linear regression test results, obtained equation Y = 69.122 + 0,451X with the acquisition of R-Square of 0.172 means that variables can influence conflict of 17.2% on the performance of employees, while the remaining 82.8% influenced by other factors such as education/training, motivation, and others. Correlation test results obtained figures 0.415 and significance of 0.000 which shows the relationship between the variables in the medium category, trending positive and significant.